The Anglo-Norman Historical Canon Publishing and Manuscript Culture - Tahkokallio, Jaakko (Humanities, 2019)
Contributes to the ongoing debate on what it meant to publish a book in manuscript. Offers case-studies of twelfth-century Anglo-Norman historians. Argues that their contemporary success was a result of successfully conducted publishing activities. This Element is also available as Open Access.